2020
DOI: 10.1177/0033294119900975
|View full text |Cite
|
Sign up to set email alerts
|

Social Anxiety and Perceived Social Support: Gender Differences and the Mediating Role of Communication Styles

Abstract: Social anxiety has been linked with lower perceived social support, and there is some evidence that communication styles may explain this relationship. In addition, a body of literature has found gender differences in social anxiety, communication, and perceived social support. The purpose of this exploratory study was to investigate six communication styles as mediators of the relationship between social anxiety and perceived social support and whether such relationships vary by gender. College men and women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 43 publications
1
31
0
2
Order By: Relevance
“…Compared to the female medical fresh students, the males' PTG is signi cantly higher than females'. The results are consistent with previous studies that females were experiencing more severe stress and anxiety symptoms, while males showed better resilience to stress [29,30].…”
Section: Discussionsupporting
confidence: 93%
“…Compared to the female medical fresh students, the males' PTG is signi cantly higher than females'. The results are consistent with previous studies that females were experiencing more severe stress and anxiety symptoms, while males showed better resilience to stress [29,30].…”
Section: Discussionsupporting
confidence: 93%
“…They will avoid interactions with others to the greatest extent possible, and even try not to ask for help when they have difficulties, which may lead to a lack of social support (SS) in their real lives. Some studies ( Wonderlich-Tierney and Vander Wal, 2010 ; Moghtader and Shamloo, 2019 ; Barnett et al, 2021 ) showed that the higher the level of SA of college students, the lower their perceived SS. SS, as an important resource of social characteristics, is an important factor in improving individuals’ perceptions of the controllability of events and enhancing their internal psychological resources ( Hill and Hamm, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, the communication style in the transactional model assumes that complex information is sent and received simultaneously through various diverse media, and then becomes a consideration for everyone in the interaction process 3 . Thus, communication styles would mediate maladaptive perfectionism on perceived social support and social Anxiety on Perceived Social Support [35]. Accordingly, teachers with better communication are likely to increase the effect of teaching motivation, workplace ethics, Emotional Intelligence on the reading proficiency and knowledge sharing.…”
Section: Modernization Of Educationmentioning
confidence: 99%